1990
DOI: 10.1128/jb.172.10.6160-6161.1990
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Acinetobacter calcoaceticus mutants deficient in the p-hydroxybenzoate hydroxylase gene (pobA), a member of a supraoperonic cluster

Abstract: p-Hydroxybenzoate hydroxylase, the product of the pobA gene, gives rise to protocatechuate, which is metabolized by enzymes encoded by the pca operon in Acinetobacter calcoaceticus. Mutations in pcaD prevented growth of A. calcoaceticus with succinate in the presence of p-hydroxybenzoate. Mutants selected on this medium contained the original mutation in pcaD and also carried spontaneous mutations in pobA. These independently expressed genes were cotransformed with a frequency of 15% and thus are components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…4), in agreement with the notion that coordinated expression of genes is an economical strategy for maintaining the fluidity of sequential enzymatic steps. This coordination may be particularly relevant for the gene encoding PcaB, because its substrate, ␤-carboxymuconate, is known to be a toxic intermediary metabolite (22). Examination of the regulatory strategies invoked by members of the Roseobacter lineage may reveal unique mechanisms to ensure stringent coordination of genes involved in the formation and degradation of ␤-carboxymuconate.…”
Section: Discussionmentioning
confidence: 99%
“…4), in agreement with the notion that coordinated expression of genes is an economical strategy for maintaining the fluidity of sequential enzymatic steps. This coordination may be particularly relevant for the gene encoding PcaB, because its substrate, ␤-carboxymuconate, is known to be a toxic intermediary metabolite (22). Examination of the regulatory strategies invoked by members of the Roseobacter lineage may reveal unique mechanisms to ensure stringent coordination of genes involved in the formation and degradation of ␤-carboxymuconate.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations of the ␤-ketoadipate pathway suggested that short nucleotide sequence elements had been transferred within and among genes during their evolution (21,23,24,38,43,57). A model emerging from such findings proposed that a transposition might trigger secondary genetic events in which nucleotide sequence copies were acquired in DNA segments flanking junction points created by the transposition (42).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It therefore is surprising that the biosynthetic AroD function in the gram-negative bacterium Acinetobacter calcoaceticus is served by a constitutively expressed enzyme that appears to be type II as judged by its thermostability (53). Catabolism of dehydroquinate in these bacteria is initiated by an inducible QuiB enzyme that, as indicated by its thermolability, appears to be type I (28,53,54).Further exploration of relationships among the A. calcoaceticus dehydratases was made possible by localization of the qui genes in a supraoperonic cluster between pca genes (associated with the catabolism of protocatechuate) and pob genes (associated with conversion of p-hydroxybenzoate to protocatechuate) (2,20,23). Engineered deletion mutations were introduced into A. calcoaceticus by natural transformation, and the properties of the resulting mutant strains allowed identification of quiA, the gene for the dehydrogenase that catalyzes the conversion of quinate and shikimate to dehydroquinate and dehydroshikimate, respectively ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional benefits are provided by quirks of aromatic catabolism that allow for positive selection of mutants that have lost specific metabolic functions (12,42). Ruben Kok and David D'Argenio first put these technical advantages together by applying random PCR mutagenesis to determine amino acid residues that were essential for the function of a repressor, PobR (20).…”
Section: Acinetobacter Re-entersmentioning
confidence: 99%